Multiplexed droplet Interface bilayer formation - Barlow,NE; Bolognesi,G; Flemming,AJ; Brooks,N; Barter,LMC; Ces,O (Lab on a Chip, 2016)
We present a simple method for the multiplexed formation ofdroplet interface bilayers (DIBs) using a mechanically operatedlinear acrylic chamber array. To demonstrate the functionality ofthe chip design, a lipid membrane permeability assay is performed.We show that multiple, symmetric DIBs can be created andseparated using this robust low-cost approach.